Retinal vein occlusions : Evidence-based management - Browning, David J. (Springer New York, 2012)
After diabetic retinopathy, the varieties of retinal vein occlusion constitute the most prevalent category of retinal vascular disease. For macular edema associated with central retinal vein occlusion (CRVO), no effective therapy existed until 2009, despite decades of research and failed pilot therapies. This comprehensive, illustrated text integrates recent advances in treatments with the parallel progress in understanding of disease mechanisms. Complete with case studies, this text is perfect for retina specialists, ophthalmologists, optometrists, and residents and fellows in these fields.